2019
DOI: 10.1177/2055116919833534
|View full text |Cite
|
Sign up to set email alerts
|

Neurolymphomatosis caused by T-cell lymphosarcoma in a cat: imaging description and treatment review

Abstract: Case summary A 16-year-old domestic shorthair cat was evaluated for acute-onset right pelvic limb monoparesis localized to the sciatic nerve. MRI revealed a homogeneously contrast-enhancing, well-demarcated mass effacing the right sciatic nerve from its intravertebral origin to the end of the viewable field (mid-femur). Abdominal ultrasound revealed thickened small intestinal loops and enlarged mesenteric lymph nodes. Cytology of the small intestine was suggestive of lymphosarcoma. T-cell lymphosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“… 1 , 4 However, in our study >50% of the cases showed spinal nerve infiltration, which was more common than previously reported. 8 , 11 , 12 Neurolymphomatosis in cats mainly has been reported as single case reports, 16 , 22 , 24 , 34 , 35 , 36 , 37 brachial plexus involvement being most common, 16 , 35 either with 8 , 12 , 21 or without 11 , 35 infiltration of the subarachnoid space and spinal parenchyma, and alone 35 or in association with other peripheral nerve involvement. 22 , 34 Although less commonly reported, 1 , 24 , 34 , 38 lumbosacral plexus neurolymphomatosis was the most common lesion pattern in our group of cats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 4 However, in our study >50% of the cases showed spinal nerve infiltration, which was more common than previously reported. 8 , 11 , 12 Neurolymphomatosis in cats mainly has been reported as single case reports, 16 , 22 , 24 , 34 , 35 , 36 , 37 brachial plexus involvement being most common, 16 , 35 either with 8 , 12 , 21 or without 11 , 35 infiltration of the subarachnoid space and spinal parenchyma, and alone 35 or in association with other peripheral nerve involvement. 22 , 34 Although less commonly reported, 1 , 24 , 34 , 38 lumbosacral plexus neurolymphomatosis was the most common lesion pattern in our group of cats.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 11 , 12 Neurolymphomatosis in cats mainly has been reported as single case reports, 16 , 22 , 24 , 34 , 35 , 36 , 37 brachial plexus involvement being most common, 16 , 35 either with 8 , 12 , 21 or without 11 , 35 infiltration of the subarachnoid space and spinal parenchyma, and alone 35 or in association with other peripheral nerve involvement. 22 , 34 Although less commonly reported, 1 , 24 , 34 , 38 lumbosacral plexus neurolymphomatosis was the most common lesion pattern in our group of cats. Similar to a recent publication, 24 MRI findings in this group included symmetrical or asymmetrical thickening and enhancement of the lumbosacral nerve roots or femoral and sciatic nerves or both, meningeal enhancement of the conus medullaris, with or without the presence of an extradural, intradural, or intramedullary mass, or some combination of these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common magnetic resonance imaging (MRI) features of PNST in cats and dogs include thickening of the nerve, with associated increased T2 and mildly decreased or unaltered T1 signal intensity 11,12 . These imaging characteristics are nonspecific and observed with other conditions including lymphoma and neuritis 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…Outros quatro pacientes felinos com quadro clínico neurológico devido a infiltração dos nervos periféricos por linfócitos malignos confirmados apresentaram polineuropatia [18,20], mononeuropatia e lesão em nervos cranianos [24,38]. Todos, com imunofenotipagem conhecida para linfócito B. Ainda, há também descrição de pacientes com neurolinfomatose de linfócitos T como o caso de dois felinos em que um deles, foi evidenciado acometimento infiltrativo dessas células em nervo isquiático após apresentar monoparesia pélvica provavelmente secundária ao linfoma alimentar também confirmado por biópsia intestinal [2] e o outro, com monoplegia aguda e evolução para tetraplegia, além de paralisia mandibular como consequência da ação neurotrópica primária do linfoma, provocada também pelos linfócitos T neoplásicos [25]. Fato também relatado em paciente canino com claudicação progressiva em membro torácico direito, diagnosticado com neurolinfomatose de células T tanto em nervo radial quanto em plexo braquial [44].…”
Section: Discussionunclassified